Penggunaan Metode Natural Language Paradigm Untuk Meningkatkan Kemampuan Ekspresif Pada Anak Dislogia Dengan Autism Spectrum Disorder - Yulidar; Raudya Izzani (Jurnal Terapi Wicara, 2025)
Background: Expressive language impairment is a common problem found in children with dyslogia with condition  Autism Spectrum Disorder (ASD). Research shows that this condition significantly impacts communication skills. Difficulties in conveying thoughts, feelings, or needs often make it difficult for children with ASD to interact effectively with their surroundings. The inability to express language optimally not only hinders the socialization process but also affects cognitive development and adaptive skills, and can be frustrating for children. Given the significant impact of expressive language disorders, targeted and comprehensive interventions are needed to improve children's language skills. These interventions can include speech therapy, the use of visual media, language modeling, and alternative and augmentative communication strategies. Objective: This study aims to determine whether the Natural Language Paradigm method can improve expressive language skills. The method used a single-subject quasi-experimental design, A1-B-A2. A1 was the pretest before the intervention. B was the intervention, and A2 was the posttest after 10 sessions of intervention using the Natural Language Paradigm. Results: After 10 sessions of therapy, the intervention demonstrated moderate success. Conclusion: The 10 sessions of intervention using the Natural Language Paradigm were quite successful in improving expressive language skills.